Reforming Medicare options, tradeoffs, and opportunities - Aaron, Henry J. (Brookings Institution Press, 2008)
"Identifies and analyzes the three leading approaches to Medicare reform: updated social insurance, premium support, and consumer-directed Medicare, rating each on its political viability as well as ability to promote access to health care, improve quality of care, and control costs. Describes incremental strategies that blend elements of each plan"--Provided by publisher.